(untitled) (World Bulletin of Education and Learning, 2026)
The study of jumps in volleyball players and the kinematic factors that provide it according to the current Abalakov method, determining the effectiveness of special exercises designed to form kinematic elements that provide jumps, determining the height of vertical jumps from a place and from a run using the Abalakov method, arm movements from a standing position and determining the height of a vertical jump without arm movements, determination of the height of a vertical jump with movements of the right and left hands, determination of the height of a vertical jump with movements of the right and left legs.